Meningkatkan Kemampuan Motorik Kasar Melalui Gerakan Shalat Sebagai Bentuk Implementasi Nilai Agama - Khair, Muhammad Maulidin; Lis, Sulis; Khatimah, Nurul; Zulkarnain, Ali Iskandar (Yayasan Cendekia Gagayunan Indonesia, 2025)
Early childhood motor physical development, particularly gross motor development, which involves the movement of large muscles such as arms, legs, and neck, as well as elements of strength, coordination, balance, and endurance. Childhood is a crucial period to maximize gross motor progress through education that is adapted to age characteristics. Prayer, as a compulsory Islamic worship consisting of a series of structured movements such as takbir, rukuk, prostration, and salam, is seen as an effective means to increase gross motor capacity while instilling religious and moral values. This study applies a qualitative approach with the library research method to analyze relevant literature sources. The main goal is to improve children's gross motor skills through prayer movements as a form of implementation of religious values, focusing on aspects of physical, moral, and spiritual development of children aged 5-6 years. The results of the study show that prayer movements involve elements of endurance (placing hands on the chest, standing, bowing, prostration), coordination (right-left greeting), and balance (standing, tasyahud), which strengthen muscle strength, flexibility, and body control. This implementation not only accelerates gross motor development but also forms an attitude of discipline, solemnity, and concentration, as well as promotes emotional and spiritual balance. Overall, prayer functions as a holistic learning medium that supports children's growth in harmony, in line with child development theories and religious education recommendations, so that it has the potential to be an effective strategy in early childhood education to achieve physical and spiritual balance.